Analisis Kepadatan Lapangan Menggunakan Metoda Sand Cone Di Jalan Perumahan Ekajaya Permata 1 Sicincin Kota Payakumbuh - Asnur, Hanifah; Sari, Ridha; Yunita, Rini; Desman, Sutria (Universitas Andalas, 2023)
Every housing complex must have adequate road access because roads are a means of public transportation used by the community to support daily activities. Road infrastructure makes transportation easier and allows people to carry out activities. The road foundation layer will experience a decrease in the soil's bearing capacity as traffic flow increases, because the road structure distributes the load to all layers beneath it and supports the weight of vehicles passing on it. In circumstances like this, road construction must be of the utmost importance, and data about the existing soil on the site must be tested first. In this research, the author took a residential road that had just been built and still had a layer of compacted pavement. By making this road, people can more easily access transportation and feel comfortable when using it. Field density analysis was carried out on Jalan Perumahan Ekajaya Permata 1 Sicincin, Payakumbuh City. The sand cone method or sand cone test is used to calculate the degree of soil density. Various measurements are calculated, including sand bulk density, soil bulk density, water content, dry soil bulk density, and degree of field density. Tests were carried out at ten points at a distance of 25 meters each. The average soil water content is 7.73%. According to SNI 03-2008-1992, the recommended value of soil density is 95%. The test results show that the average degree of density in the field is 72.51%. Because the soil density in the field does not yet meet the soil density requirements of 95%, it is necessary to increase the compaction further until it meets the specified density requirements.